Mahabbah kepada Nabi dalam Puisi Ṣallū ‘Alā Khayri Al-Bariyyati Khayman dalam Perspektif Semiotika Saussure - Zulkarnain, Dhea Anindya; Kulsum, Umi; Rokhim, Minatur; Lubna, Lubna; Abdila, Muhammad Farhan (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the representation of the concept of mahabbah towards the Prophet Muhammad SAW in the poem Ṣallū ‘Alā Khayri Al-Bariyyati Khayman by Ibn al-Jinān using Ferdinand de Saussure’s semiotic theory. This study uses a qualitative descriptive method, focusing on the relationship between signs and signifiers in the formation of spiritual meanings related to mahabbah. The text of the poem Ṣallū ‘Alā Khayri Al-Bariyyati Khayman, obtained from the source of the madh nabawi poetry manuscript, is the primary source of research. Books, scientific journals, and articles discussing mahabbah and Saussure’s semiotics are used as supporting sources. Data collection techniques were carried out through documentation studies, namely by collecting, recording, and grouping linguistic signs in the poem text. Based on the research findings, this poem displays various expressions of mahabbah, such as adoration, longing, hope for intercession, and recognition of the glory and virtue of the Prophet Muhammad SAW. The system of signs, formed through word choice and stanza structure, shows how the meaning of mahabbah emerges through a systematic relationship between signs that complement each other. This study concludes that the poem is not only an expression of art, but also a medium of da’wah that strengthens love and respect for the Prophet Muhammad SAW.